Implementation of SIKOMO Information System for Dr Soetomo University’s Lecturer and Employee Cooperative - Adhania Andika Prayudanti; Rika Puspita Sari; Ninik Mardiana; Ratna Nur Tiara Shanty (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The Dr. Soetomo University Lecturer and Employee Cooperative supports member welfare through goods and services but faces challenges in inventory due to manual records prone to errors. To address this, a community service team introduced an Inventory Information System to automate stock tracking and improve efficiency. Method: Activities included assessing equipment and data needs, digitizing manual records, presenting the system, and conducting initial training for cooperative staff. Practical Application: The program aimed to introduce the system, solve data recording issues, and improve staff competency in system operation. Conclusion: The initiative was well-received, with management committing to appoint two new system operators. Key features and the implementation plan were appreciated. However, adjustments to the item master data are still needed for optimal integration.